Developing Distributed System with Service Resource Oriented Architecture - Hermawan Hermawan; Riyanarto Sarno (Universitas Ahmad Dahlan, 2012)
Service oriented architecture (SOA) is a design paradigm in software engineering for an enterprise scale which built in a distributed system environment. This paradigm aims at abstracting of application functionality as a service through a protocol in web service technology, namely simple object access protocol (SOAP). However, SOAP have static characteristic and oriented by the service methode, so have restrictiveness on creating and accessing for big numbers of service. For this reason, this reasearch aims at combining SOA with resource oriented architecture (ROA) that is oriented by the service resource use representational state transfer (REST) protocol in order to expand scalability of service. This combination is namely service resource oriented architecture (SROA). SROA can optimize distributing of applications and integrating of services where is implemented to develop the project management software. To realize this model, the software is developed according with framework of Agile model driven development (AMDD) to reduce complexities on the whole stage processing of software development.